2016
DOI: 10.4037/ajcc2016665
|View full text |Cite
|
Sign up to set email alerts
|

Association of Injury Factors, Not Body Mass Index, With Hospital Resource Usage in Trauma Patients

Abstract: Background Allocating resources appropriately requires knowing whether obese patients use more resources during a hospital stay than nonobese patients. Objectives To determine if trauma patients with different body mass indexes differed in use of resources measured as a multifaceted outcome variable. Methods A trauma registry was used for a retrospective stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 48 publications
(95 reference statements)
1
1
0
Order By: Relevance
“…Total cost of care increased with increasing ISS, which was consistent with the findings of Garnett and Browne [11], and Kuwabara et al [30]. This again confirmed that the ISS enables the prediction of necessary resources for trauma patient management [9] and is a major predictor of healthcare utilization in trauma patients [9,[11][12][13]. Therefore, analysis and interpretation based on the ISS is expected to produce more reliable results pertaining to trauma patients' healthcare utilization, particularly the total cost of care.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Total cost of care increased with increasing ISS, which was consistent with the findings of Garnett and Browne [11], and Kuwabara et al [30]. This again confirmed that the ISS enables the prediction of necessary resources for trauma patient management [9] and is a major predictor of healthcare utilization in trauma patients [9,[11][12][13]. Therefore, analysis and interpretation based on the ISS is expected to produce more reliable results pertaining to trauma patients' healthcare utilization, particularly the total cost of care.…”
Section: Discussionsupporting
confidence: 81%
“…Apart from its use in assessing injury severity in trauma patients, the ISS is an anatomical scoring system effective in predicting mortality, hospital stay, length of recovery, and demands for resources to manage trauma patients [10]. Moreover, it is a major predictor of healthcare utilization in such patients [11][12][13] and is actively utilized in healthcare providers' communications and triage [9]. Therefore, analyzing healthcare utilization in trauma patients according to the ISS is a systematic method of analysis, where trauma patients' healthcare service needs are relatively homogeneously divided.…”
Section: Introductionmentioning
confidence: 99%